Myth of European Dark Age (5th-15th Century) Scientific Knowledge Stagnation: Critical Studies of Scientific Idea Interactions between the Late Medieval Theologian and Early Modern Philosopher - Chung-Chong, Jaw; Amran, Muhammad (2021)
Within common historical context, most historians consider the European renaissance age as age of origins of modern scientific knowledge, also, they assume European Medieval Age (5th-15th centuries) as age full with scientific knowledge ignorant. This research paper gives important historical review about interactions of scientific idea between the late medieval theologian and early modern philosopher. However, most previous research was more emphasized on scientific knowledge development during the age of renaissance and age of enlightenment without considering the contribution of early medieval age theologian. By examining this historically event with critical review, I do give some clarification to such pervasive myth by using qualitative research methodologies, which involving analyst of historical facts from primary resources and secondary resources such as archives, journals, book chapters, and published research paper. This research challenges the argument that scientific knowledge development only happened since renaissance age. In the comparatives studies, I found out that early medieval theologian, from William of Ockham to Gabriel Biel, who did played an important role of influencing early modern philosopher, Rene Descartes to David Hume, with scientific ideas. Such finding does give a significant clarification to the myth of medieval Europe scientific knowledge stagnation in modern historical debate.